Escutar quem o estado silencia: luto coletivo, redução de danos e resistência poética à necropolítica - Genuino, Renata Reis (Universidade Federal de São Carlos, 2025)
This work is an experiential report on the actions of the Coletivo Livre de Redução de Danos alongside the homeless population in the city of São Carlos, through the Sarau da Calunga — a cultural and political gathering built within the territory. Grounded in attentive listening and the formation of bonds, the report weaves together the concepts of Harm Reduction, necropolitics (Mbembe, 2018), collective mourning (Butler, 2019), and the power to act (Espinosa, 2009), exploring how cultural practices become strategies of care, resistance, and symbolic elaboration of loss. The Sarau emerges as a space of memory and affirmation of life, in contrast to the logics of exclusion and death imposed by the State. The methodology is based on situated experiential narrative, with both visual and narrative resources, recognizing gaps and incompleteness as part of the knowledge production process. By listening to those silenced by the State, the work claims the right to public mourning and the dignity of precarious lives.
Listening to those who the state silences: collective mourning, harm reduction and poetic resistance to necropolitics
Keywords: Redução de danos; Situação de rua; Necropolítica; Luto coletivo; Escuta; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO